Melihat Perbuatan Buruk sebagai Salah Satu Pembelajaran dalam Perspektif Hadis Nabi - Ahmad Siddiq Setiawan; Andi Ali Amiruddin; Amrullah Harun; Risda Alfi Fat Hanna; Alif Wiladatil Ifah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss bad deeds as one of the lessons in the perspective of the Prophet’s hadith. This research method is library research, namely research that use books as a data source, and has relevance to the research material, namely takhrij hadith. The result and discussion of this study indicate that bad deeds are one of the lessons in the perspective of the Prophet’s hadith, namely through the learning, these bad deeds can have a positive value if they are used as a source to gain knowledge, a source to gain knowledge, and as self-development and change the way people view bad things. This study recommends to academics and research circles to develop further related to this research and be able to make bad deeds as a learning materials such as those in the hadith of the Prophet.